Indoor Real-Time Locating System comparison: Polaris vs FIND3 - Silva, David (2021)
The use of real-time locating systems can be used in several fields, from security and health to building and energy management. However, there is no consensus in what the better solution or technology is to be used in an indoor location system. This paper presents a comparative study between a market real-time locating system and an open source real-time locating system. The systems that will be compared are Polaris and FIND3. The tests were performed in an office building.